Possibilities of green technologies application in building design from sustainability dimensions - Moňoková, Andrea; Vilčeková, Silvia; Krídlová Burdová, Eva (International Conference “Environmental Engineering”, 2017)
The aim of this paper is to summarize knowledge of green technologies and their applications in buildings, as well as high performance green buildings. Two alternatives of family house design are performed. The first alternative uses conventional building materials and it doesn’t follow the sustainability principles. On the other hand, the second one is designed by using the environmentally friendly materials and with sustainability principles in mind. Designs of conventional and green family house are mutually compared from energy efficiency, embodied energy and greenhouse gas emissions such as CO2eq. and SO2eq. point of view. A special focus is put on the sustainability assessment of designed houses by the Slovak environmental assessment system of buildings.